Trends in The Percentage of Primary School Students Accessing The Internet in Yogyakarta Province (As an Analysis of The Current State of Learning): Tren Persentase Siswa Sekolah Dasar yang Mengakses Internet di Provinsi Yogyakarta (Sebagai Analisis Kondisi Pembelajaran Saat Ini) - Mahmudi, Moh Rosyid; Khair, Baiq Niswatul; Haryanto, Haryanto; Firdaus, Fery Muhammad (Universitas Muhammadiyah Sidoarjo, 2024)
This study is a trend analysis of data on the percentage of primary school students who access the internet in Yogyakarta. The data is obtained from BPS-RI in the Education Statistics book which is published annually. Trend analysis was conducted for data from 2006 to 2023. The purpose of this research is to explore and examine more deeply the current state of learning. The research method used was explanatory sequential. The data has a general increasing trend. However, in 2022 and 2023 there was a decrease. The increase from 2016 is assumed to be due to easier and more internet facilities. After many people understand the shortcomings of online learning, blended learning was initiated which combines in-person learning and online learning. So that the prediction in 2024 the percentage value will increase again.